Global yields, chemical compositions and antioxidant activities of clove basil (Ocimum gratissimum L.) extracts obtained by supercritical fluid extraction - Leal, Patricia F.; Chaves, F. Celio M.; Ming, Lin Chau [UNESP]; Petenate, Ademir J.; Meireles, M. Angela. A. (Blackwell Publishing, 2006)
Clove basil (Ocimum gratissimum) extracts were obtained with supercritical CO2. Clove basil was cultivated using 0, 4, 8 and 12 kg/m(2) of organic fertilizer and was harvested in four seasons: winter, spring, summer and autumn, in the Southern Hemisphere. The extracts' global yields were determined at 40C and 150 bar for samples from all cultivation conditions and harvesting seasons. For selected samples, the extracts' global yields at 40C were determined for pressures of 100, 150, 200, 250 and 300 bar. The extracts were analyzed by gas chromatography-flame ionization detector. Antioxidant activity (AA) was assessed using the coupled reaction of beta-caroteneand linolenic acid. The extracts' global yields varied from 0.91 to 1.79% (dry basis), and the AAs varied from 62 to 84% compared with the control beta-carotene. Eugenol and beta-selinene were the major compounds. The relative proportion of eugenol varied from 35 to 60%, while the content of beta-selinene remained approximately constant (11.5-14.1%, area). The other substances quantified in the extracts were 1,8 cineole, trans-caryophyllene and alpha-selinene.